INTEGRASI AJARAN SOSIAL GEREJA DALAM PENDIDIKAN FORMAL: Membentuk Generasi Muda Katolik Sebagai Agen Sosial - Lan, Yap Fu (CREDENDUM: Jurnal Pendidikan Agama, 2023)
Youth bulge and demographic dividend have been a two-in-one topic of discussion in government and industrial milieus in Asia generally, and in Indonesia particularly. Education is believed as a strategic way to make youth bulge to be demographic dividend. Education prepares young people to get proper jobs so they can increase income for their families thus increase per capita income figure. Unfortunately, education has been occupied to meet only the market demands. Education has turned into business; schools and universities have become the instruments to spread the ideology of capitalism. Intervening formal education becomes a must for the Catholic Church to do according to her own teachings. This literature study is conducted to recall the Church’s intent regarding education and to propose Catholic social teachings and their values as the content of education that the Church have to strive for. The exploration will be described in three parts: the reasons the Church needs to intervene formal education, the Church’s vision on young people, and the urgency of Catholic social teachings for the life of society today thus to integrate the teachings into education that forms young Catholics as social agents to be.